LITERATURE REVIEW: PENGARUH TERAPI RELAKSASI BENSON TERHADAP KUALITAS TIDUR LANSIA - Sarwendi AL Ghazali; Nur Elly; Ervan Ervan (Poltekkes Kemenkes Bengkulu, 2021)
Background: The function of sleep is very important for the life of the elderly because sleep disorders can affect the quality of life. Getting quality sleep is important for improving health, including recovery from illness. Disruption of sleep quality can cause physiological and psychological balance disorders in the elderly. Benson relaxation is a method of deep breathing intervention combined with surrender to God which gives a relaxed and comfortable feeling so as to improve sleep quality in the elderly. The purpose of this study was to prove the effect of Benson relaxation on the sleep quality of the elderly. Methods: This study used a literature review design. Study selection from online database as data for this research. Researchers use articles relevant to the MeSH and PICOS Framework keywords which will be described in the PRISMA Diagram, eligible articles will be assessed using critical assessment to determine the quality of the study.Results: Of the 6 studies that met the criteria for analysis, respondents with sleep quality disorders on average were aged 60-70 years, and most of them were experienced by elderly women, the length of time for the intervention varied from 1 week to the shortest. and 6 months for the longest, of the varying lengths of intervention, all stated that there was an increase in sleep quality after Benson's relaxation intervention.Conclusion: Benson relaxation therapy can improve sleep quality in the elderly.